Ontogenes and of Individual Developmental Program in D. melanogaster - Chadov , B. F.; Fedorova , N. B. (Advanced Research in Biological Science Vol. 6, 2023)
This chapter described the data on the Drosophila ontogeny extractable from the information about conditional mutations. In Drosophila melanogaster, a novel class of mutations known as conditional mutations was found. In a restrictive genotype, this type of mutation dies, but in a permissive genotype, it survives and proliferates. In addition to being conditional, permissive genotype mutations exhibit a few unique characteristics that set them apart from traditional mutations. The appearance of morphoses in mutants indicates that the genes regulate ontogeny. These genes were dubbed ontogenes in accordance. These genes were given the name ontogenes in accordance. These mutations' characteristics were examined in the following ways: (1) Conditionality; (2) Lethality; (3) Reduced fertility; (4) The development of morphoses; (5) A parental effect on the inheritance of the mutant phenotype; (6) Effect of chromosomal aberrations on mutation manifestation; (7) Long-range gene interaction; and (8) The shift of mutation-induced lethality to zygotic stage. The data under consideration are sufficient, logically connected, and consistent in stating that the ontogenes: (1) Are DNA regions, (2) Are active in germ cells, (3) Encode intranuclear RNAs, (4) Induce epinucleotide (epigenetic) changes in the genome, and (5) Determine the order of developmental stages (program of development); (6) The corresponding program is read twice, namely, (a) in the germline cells (reload) and (b) in somatic cells (implementation); and (7) The first read proceeds from the last stage of individual development to the first stage and the second read occurs in the opposite direction from the first stage of individual development to the last stage.